Constitutively active GPR43 is crucial for proper leukocyte differentiation. Issue 1 (5th December 2022) - Miyasato, Sosuke; Iwata, Kurumi; Mura, Reika; Nakamura, Shou; Yanagida, Keisuke; Shindou, Hideo; Nagata, Yosuke; Kawahara, Masahiro; Yamaguchi, Satoshi; Aoki, Junken; Inoue, Asuka; Nagamune, Teruyuki; et al.
Abstract: The G protein‐coupled receptors, GPR43 (free fatty acid receptor 2, FFA2) and GPR41 (free fatty acid receptor 3, FFA3), are activated by short‐chain fatty acids produced under various conditions, including microbial fermentation of carbohydrates. Previous studies have implicated this receptor energy homeostasis and immune responses as well as in cell growth arrest and apoptosis. Here, we observed the expression of both receptors in human blood cells and a remarkable enhancement in leukemia cell lines (HL‐60, U937, and THP‐1 cells) during differentiation. A reporter assay revealed that GPR43 is coupled with Gαi and Gα12/13 and is constitutively active without any stimuli. Specific blockers of GPR43, GLPG0974 and CATPB function as inverse agonists because treatment with these compounds significantly reduces constitutive activity. In HL‐60 cells, enhanced expression of GPR43 led to growth arrest through Gα12/13 . In addition, the blockage of GPR43 activity in these cells significantly impaired their adherent properties due to the reduction of adhesion molecules. We further revealed that enhanced GPR43 activity induces F‐actin formation. However, the activity of GPR43 did not contribute to butyrate‐induced apoptosis in differentiated HL‐60 cells because of the ineffectiveness of the inverse agonist on cell death. Collectively, these results suggest that GPR43, which possesses constitutive activity, is crucial for growth arrest, followed by the proper differentiation of leukocytes.